The effect of stimulating budshoot growth method on survival and stem growth of ’pera’ orange scion - de Carvalho, Edson Ferreira (Pesquisa Agropecuaria Brasileira, 1992)
This experiment was conducted in order to compare four methods of stimulating budshoot growth in citrus. Rangpur lime was used as rootstock and ’Pera’ orange as scion. The partial cutting and partial cutting with bending of the top of the stock away from the bud were equivalent in terms of percent survival and rate of growth. Looping the stock above the bud union resulted in a reduction of 42.5 in percent of bud survival, but this method resulted in a marked increase in rate of growth. The total cut rootstock above the budding point resulted in 100% of survival, but this treatment resulted in great reduction in growth, and only 10% of plants achieved a height of 60 cm after 50 days. There was no difference in the diameter of the citrus nursery trees among four stimulating budshoot methods. The total cut rootstock was the method that gave the best results stimulating budshoot development, and the looping stock method was the least efficient.